Analisis kesulitan teknik smash atlet bola voli Klub FVC Kota Lubuk Linggau - Novalia, Anike; Supriyadi, M; Sovensi, E (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
The research is aimed at finding out how difficult the bolavoli smash technique at the FVC club of lubuklinggau au in 2020. The study is a qualitative descriptive study that explains current situations or activities by conducting interviews. In this study a population of 14 people and a sample of 10 people who participated in bolavoli training at the FVC club. Data collection techniques use observation and interviews to identify the difficulties and difficulty of each individual. The study suggests that the description of the difficulty of the smash technique at the bolavoli FVC city of lubuklinggau was in the preparation of that which was a faulty footstep and a less high jump and then at the inclination of the athlete was having a hard time moving the hand swing so hard to reach the ball and the cause of difficulties was due to an inflection of the start of the approach with a very quick ball and hit the ball below the club's shoulders.